SURAU SEBAGAI LEMBAGA PENDIDIKAN ISLAM DI SUMATERA BARAT - Juliwansyah, Juliwansyah; Iswantir, Iswantir (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
This article aims to provide an overview of Surau Educational Institutions in Minangkabau. the role of the surau which is one of the most important aspects of rural life in Minangkabau. Surau became the center for the spread and development of Islam in the interior areas of West Sumatra. The surau acted as an important conduit for the intensive Islamization of the remote areas of the Minangkabau west coast ports. This research includes qualitative research with the type of library research. The results of the study show that surau is a socio-cultural institution that was known by the Minangkabau people before the arrival of Islam. The spreaders of Islam, especially from among the Sufis, spread Islam in a flexible way by adapting to local culture. So the surau was adapted and Islamized to serve as an Islamic educational institution, both in teaching the Qur'an as a guide for the life of the people, studying the basic sciences of Islam, including as a tarekat educational institution.